2001
DOI: 10.1093/ajcn/73.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of different nutritional supplements on symptoms and functional capacity in patients with chronic obstructive pulmonary disease

Abstract: An energy load up to 2092 kJ had no adverse immediate effect in COPD patients compared with placebo. The subjects who consumed the fat-rich supplement experienced more shortness of breath than did the subjects who consumed the carbohydrate-rich supplement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 17 publications
4
39
0
3
Order By: Relevance
“…The VCO 2 increase can worsen the condition of patients in respiratory failure, but its effect on stable patients is small, of little clinical importance. It is important to point out that a more recently published study did not find any difference in exercise performance and that, although high dietary carbohydrate did determine an increase in the respiratory quotient, dyspnea was significantly higher when the patients received a highfat diet (43) .…”
Section: Studies In Nutritional Supplementationmentioning
confidence: 78%
“…The VCO 2 increase can worsen the condition of patients in respiratory failure, but its effect on stable patients is small, of little clinical importance. It is important to point out that a more recently published study did not find any difference in exercise performance and that, although high dietary carbohydrate did determine an increase in the respiratory quotient, dyspnea was significantly higher when the patients received a highfat diet (43) .…”
Section: Studies In Nutritional Supplementationmentioning
confidence: 78%
“…Earlier studies indeed showed adverse effects of a carbohydrate-rich energy overload on carbon dioxide production and exercise capacity [10], but these results were not confirmed when using a normal energy load [11]. In fact even positive effects of a carbohydrate-rich supplement relative to a fat-rich supplement on lung function and dyspnoea sensation were reported [12].…”
Section: Loss Of Body Weight and Fat Massmentioning
confidence: 94%
“…Vermeeren and coworkers (22) examined the differences between a fat-rich versus carbohydrate-rich diet on exercise performance in COPD. They hypothesized that a fat-rich diet would be better tolerated than a carbohydrate-rich diet due to a lower Respiratory Quotient and thus lower CO 2 production.…”
Section: Nutritional Interventionsmentioning
confidence: 99%